Environmental Quality Impact Analysis of Settlements Bontang Kuala, East Kalimantan Province - Stefano, Andrew; Martosenjoyo, Triyatni; Asmal, Idawarni; Syarif, Edward (Journal of Applied Engineering and Technological Science (JAETS), 2024)
The present study seeks to elucidate the multifaceted impacts of resettlement programs on various dimensions of social and economic life within the community. The primary objectives of this investigation are threefold: 1) to assess the influence of resettlement programs on the intensity and quality of social relations; 2) to conduct a comprehensive analysis of the socioeconomic ramifications of resettlement programs; and 3) to evaluate the behavioral patterns associated with the utilization of bathing, washing, and defecation facilities. The research methodology employed in this study is based on secondary data sourced from “Bontang Dalam Angka 2023” and primary data collected through questionnaires administered to local fishermen. A random sampling technique was employed to select a sample of 50 families. The data collected, encompassing various research variables, were analyzed using descriptive analytical methods, t-tests, and Product Moment Correlation. The findings of the study indicate a significant positive impact of resettlement programs on social relations within the community. Families that promptly moved into their new residences reported enhanced levels of social interaction and engagement. Additionally, the resettlement programs demonstrated a positive influence on the socioeconomic conditions of the community, particularly in terms of the expansion of educational opportunities and infrastructural improvements. Notable improvements in learning outcomes and increased access to educational facilities emerged as key positive outcomes. Furthermore, the study reveals a marked improvement in social behaviors related to sanitation practices, particularly in the use of bathing, washing, and defecation facilities, among individuals participating in the resettlement programs. A heightened adherence to hygienic sanitation practices was observed, signifying the positive behavioral shifts prompted by the resettlement initiatives. In conclusion, the evidence suggests that resettlement programs exert a favorable influence on both the social and economic aspects of community life, while also fostering improved sanitation practices. This research contributes meaningfully to the broader understanding of the complex impacts of resettlement programs on individual and communal life.